Sublimul trădării - Roșu, Ioana (Theatrical Research, 2024)
The Sublime of Betrayal In his volume, "The Sublime of Betrayal", Sorin Crișan meditates on the role of theater as a living mirror of life. The book discusses the concept of working through an artistic context, in contrast to a psychoanalytic one, and discusses the concept of Brechtian distancing and mimesis, inspired by Roland Barthes, emphasizing the interplay between thought and perception in contemporary theatre. The themes of the sacred and the profane are discussed in relation to Mircea Eliade’s theories and Husserl’s phenomenology, to highlight how theater transcends everyday reality and opens new perspectives on human existence. The volume thus becomes a thorough analysis of the theater as a space of imagination and reflection, combining aesthetics and philosophical discourse finally, exploring the diversity of theatrical forms, from ritual to performance. Sorin Crișan significantly contributes to the understanding of theater not only as a performing art, but also as an intellectual and spiritual process, inaugurating specific ways of cognition for both the actor and the spectator.